The healing hand: the role of women in ancient medicine - Retief, Francois P.; Cilliers, Louise (Acta Theologica, 2005)
In contrast with the struggle of 19th and 20th century women all over the world to be admitted to medical schools, women in ancient Greece and Rome were apparently increasingly at liberty to practise medicine from the 4th century BC onwards. The available evidence offers conclusive proof of this more tolerant attitude. The sources are few in number, but fragmentary information can be gleaned from medical writers, passing remarks in Greek and Latin authors, and funerary inscriptions. These sources emphasise the professions of midwife and female doctor. Although there is some overlap between their duties, we find that in Greece a distinction was drawn between maia and iatrikê as early as the 4th century BC, while in Rome the two professions of obstetrix and medica or iatrina were well established by the 1st century BC. The training, personal characteristics, qualifications, duties, status and remuneration of practitioners of the two professions will be considered in this study. The funerary inscriptions of female doctors reveal that they were honoured in the same way as men for exceptional services; medical works were also dedicated to them as colleagues, and those of them who wrote texts of their own were quoted with respect. Thus, although there were never very many female doctors, the classical world does not seem to have placed insurmountable obstacles in the way of women who wished to practise medicine.